A continuum damage model for three-dimensional woven composites and finite element implementation. (15th September 2015) - Zhong, Suyang; Guo, Licheng; liu, Gang; Lu, Huaiyu; Zeng, Tao
Abstract: A continuum damage model for predicting the damage initiation and development in three-dimensional (3D) woven composites is proposed, in which the fiber fracture, inter-fiber fracture and matrix fracture are considered in the level of the fiber yarn and the matrix. A set of damage variables are presented to characterize all the failure modes of the fiber yarn and matrix. The damage initiation and propagation criteria are based on the Puck criteria for the fiber yarn and the paraboloidal yield criterion for the matrix. This continuum damage model is implemented by combining it with the finite element method (FEM). To validate the continuum damage model, the quasi-static tensile experiments of a type of 3D woven composites are carried out, and the tensile failure is predicted by the damage model which agrees well with the experimental results.